WEB E-COMMERCE RKU COMPUTER PALEMBANG - Aisyah Aisyah; Leon Andretti Abdillah; Suyanto Suyanto; Deni Erlansyah (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
In the increasingly developing digital era, the role of the internet and information technology is increasingly important in supporting various aspects of business, including marketing and product sales. Especially the presence of a website has become an important need for a business that wants to compete in this increasingly competitive market, to expand market reach and increase their brand visibility. RKU Computer Palembang is a business engaged in computer sales and services. Currently, the RKU Computer sales system is still manual, namely prospective buyers come directly to the RKU Computer store to buy its products. To overcome this problem, the author tries to provide a solution to RKU Computer, namely by building an e-commerce website as an online sales media, to help RKU Computer sell its products, and to help RKU Computer compete with other businesses that have implemented an online sales system. The research methodology used in this study is a software development method using extreme programming consisting of 4 stages, namely planning, design, coding, and testing, and a process method using market basket analysis (MBA). The desired result of this study is to create an RKU Computer Palembang e-commerce website as an online sales media